" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
f(0) = 4
f(1) = 5 - (1/e)
f(0)= 4
A + Be⁻⁰ = 4
A + B = 4
A = 4 - B
f(1) = 5 - (1/e)
A + Be⁻¹ = 5 - (1/e)
4 - B + Be⁻¹ = 5 - (1/e) Aqui se reemplaza el valor de A
-B + Be⁻¹ = 5 - (1/e) - 4
B(e⁻¹ - 1) = 1 - (1/e)
B = [1 - (1/e)] / (e⁻¹ - 1)
= [1 - (1/e)] / ((1/e) - 1)
= [(e - 1)/e] / [(1 - e)/e]
= [e(e - 1)] / [e(1 - e)]
= (e - 1) / (1 - e)
Reemplazando B
A = 4 - B
= 4 - (e - 1)/(1 - e)
= [4(1 - e) - (e - 1)] / (1 - e)
= (4 - 4e - e + 1) / (1 - e)
= (5 - 5e) /( 1 -e)
= 5(1 - e) / (1 - e)
= 5